(3efGgL GdHMK hbhGYO GdGSJOdGd GdbGfhfj (B/s - (3JeGe, GdSjO YHO GdYGds ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2016)
(3jJfGhd cJGH (B((3efgGL GdHMK hbhGYO GdGSJOdGd GdbGfhfj(B) (3hGdPj bGe HJCdjag (B((3GdSjO JeGe(B) (3aj MhGdj (B(376) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdGSJOdGd GdbGfhfj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3ebOeI, GdaUd GdChd (B: (3CSGSjGJ GdHMK GdYdej, hjTed GdeHMK GdChd (B: (3GdJacjQ GdYdej, GdeHMK GdKGfj (B: (3GdHMK GdYdej, GdeHMK GdKGdK (B: (3efGgL GdHMK GdYdej(B. (3GdaUd GdKGfj (B: (3GdegGQGJ GdNGUI GdhGLH JhGaQgG aj GdHGMK(B... (3EdN(B. s
Keywords: (3GdbGfhfs -- (3efGgL HMKs; (3GdGSJOdGds